2017
DOI: 10.1080/07448481.2017.1382498
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion and suicidal behavior in college students: Serial indirect effects via depression and wellness behaviors

Abstract: Self-compassion may protect against suicidal behavior, in part, due to reduced depressive symptoms and heightened engagement in wellness behaviors. Individual and campus-wide strategies promoting self-compassion and wellness behaviors may reduce suicide risk on college campuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 34 publications
2
12
0
1
Order By: Relevance
“…If this continues, they may begin to want to end their lives. Additionally, excessive life stress can increase suicidal ideation because it weakens the selfdefence mechanisms needed to face challenges (Kelliher Rabon et al, 2018). A study by Kim and Hong (2016) found that the number of university students in South Korea who report serious life stress is increasing, as is the number of students who experience suicidal ideation as a result.…”
Section: Factors Affecting Suicidal Ideation In University Studentsmentioning
confidence: 99%
“…If this continues, they may begin to want to end their lives. Additionally, excessive life stress can increase suicidal ideation because it weakens the selfdefence mechanisms needed to face challenges (Kelliher Rabon et al, 2018). A study by Kim and Hong (2016) found that the number of university students in South Korea who report serious life stress is increasing, as is the number of students who experience suicidal ideation as a result.…”
Section: Factors Affecting Suicidal Ideation In University Studentsmentioning
confidence: 99%
“…La autocompasión no es tampoco auto-exigencia ni tener alta autoestima, comprendiendo esta última como una valoración de uno mismo en comparación a los demás.La autocompasión es un factor protector para nuestra salud. Por ejemplo, una investigación con estudiantes universitarios encontró una asociación directa e indirecta (a través de la percepción de bienestar y síntomas depresivos) entre el nivel de autocompasión y la conducta suicida(Kelliher et al, 2018). También se han encontrado asociaciones entre mayor autocompasión y menor consumo de alcohol en adultos jóvenes(Saarinen et al, 2019).…”
unclassified
“…Although emerging evidence indicates that self-compassion is linked to positive outcomes among veterans, including decreased guilt and PTSD symptoms (Dahm et al, 2015;Held & Owens, 2015;Hiraoka et al, 2015), and to decreased suicidal behavior in college students (Hasking et al, 2018;Kelliher Rabon et al, 2018), the protective role of self-compassion in reducing suicide risk has yet to be investigated in veterans. Moreover, this study is one of the first to investigate whether self-compassion has more salience and, thus, more clinical utility, in times of heightened distress, particularly given the fact that veterans often face increased levels of psychosocial stressors.…”
mentioning
confidence: 99%